2021
DOI: 10.1016/j.psj.2021.101436
|View full text |Cite
|
Sign up to set email alerts
|

Centennial Review: A revisiting of hen welfare and egg safety consequences of mandatory outdoor access for organic egg production

Abstract: Mandating free range husbandry as a requirement for organic egg designation remains a prevailing sentiment within a segment of the organic community. The proponents maintain that such management practice ensures high hen welfare and enhanced wholesomeness of the egg. However, evidence from the field, especially in the European Union ( EU ), contradicts these assumptions. In many cases, hens allowed outdoor access were more subject to increased injury from predators and from flock mates, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 80 publications
(125 reference statements)
0
10
0
1
Order By: Relevance
“…Although all samples from the farm tested negative for the presence of Salmonella, it is crucial for proper hygienic and sanitary practices to be in place to prevent the dissemination of pathogenic agents like Salmonella among flocks. Furthermore, Holt et al [60] have reported that hens with outdoor access require heightened biosecurity efforts to mitigate potential interactions with predators, wild birds, and rodents. Consequently, such hens face an elevated risk of Salmonella enterica infection, leading to Salmonella-contaminated egg production [60].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although all samples from the farm tested negative for the presence of Salmonella, it is crucial for proper hygienic and sanitary practices to be in place to prevent the dissemination of pathogenic agents like Salmonella among flocks. Furthermore, Holt et al [60] have reported that hens with outdoor access require heightened biosecurity efforts to mitigate potential interactions with predators, wild birds, and rodents. Consequently, such hens face an elevated risk of Salmonella enterica infection, leading to Salmonella-contaminated egg production [60].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Holt et al [60] have reported that hens with outdoor access require heightened biosecurity efforts to mitigate potential interactions with predators, wild birds, and rodents. Consequently, such hens face an elevated risk of Salmonella enterica infection, leading to Salmonella-contaminated egg production [60]. Salmonella contamination within hen flocks and eggshells is a multifactorial issue.…”
Section: Discussionmentioning
confidence: 99%
“…En este sentido Overmeire y otros (2006) realizaron un estudio donde evaluaron la concentración de diferentes tóxicos entre ellos mercurio en huevos de gallinas orgánicos criados al aire libre, concluyendo que presentaban altos niveles de contaminantes y que podrían presentar un riesgo para la salud pública. Recientemente, Holt (2021) hace un llamado a replantear el requisito de la crianza de gallinas ponedoras de huevos orgánicos a campo abierto, debido a que las gallinas tienden a presentar una mayor mortalidad y a enfermarse con más frecuencia, además de estar expuestas a metales pesados como el mercurio, comparado con gallinas criadas en condiciones de confinamiento, lo que se traduce en una mayor acumulación de tóxicos tanto en huevos como partes comestibles de la aves de corral. Por su parte, Kin y colaboradores (2019) observaron que la acumulación de Hg 2+ en pechuga e hígado en pollos de engorde era dosis-dependiente, por lo cual a una mayor ingesta de mercurio inorgánico mayor bioacumulación se va a dar en órganos y tejidos.…”
Section: Discussionunclassified
“…An additional key concern for the public is with product safety [ 36 ]. The free-range hens foraging in outdoor enclosures have a higher risk of exposure to biosafety risks, compared to caged hens [ 37 ]. This can increase the occurrence of salmonella-contamination in the eggs and result in food safety problems [ 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…The free-range hens foraging in outdoor enclosures have a higher risk of exposure to biosafety risks, compared to caged hens [ 37 ]. This can increase the occurrence of salmonella-contamination in the eggs and result in food safety problems [ 37 ]. In addition, the increase in stocking density and farm size has led to the occurrence and spread of salmonella in the laying flocks [ 38 ].…”
Section: Introductionmentioning
confidence: 99%